A.W. Chesterton expands W & O supply distribution territory. Issue 4 (April 2015) - Unknown
Abstract : In the USA, W & O, a global supplier to the marine and upstream oil and gas markets for pipe, valves and fittings, valve automation and engineered systems, has announced the expansion of its distribution territory with A.W. Chesterton Co to include Washington and Oregon for the Pacific Northwest maritime market.